2019
DOI: 10.1590/s0100-83582019370100019
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic Potential of Sorghum bicolor at Different Phenological Stages

Abstract: This study aimed to assess the allelopathic potential of the aqueous extract of the shoot of Sorghum bicolor at different phenological stages on seed germination and initial growth of kale (Brassica oleracea var. acephala) seedlings, which is considered a bioindicator species. The experiment was carried out at five development stages of S. bicolor (40, 50, 60, 70, and 80 days after emergence), which was used as aqueous extract at six concentrations (0, 20, 40, 60, 80, and 100%) applied in four replications per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…The blend was stirred to obtain a homogeneous mixture, left to decant for 24 hours. Subsequently, filtering was performed using filter paper, and then solutions of 25, 50, 75, and 100 g.L -1 were prepared by diluting the final extract (Zucareli et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The blend was stirred to obtain a homogeneous mixture, left to decant for 24 hours. Subsequently, filtering was performed using filter paper, and then solutions of 25, 50, 75, and 100 g.L -1 were prepared by diluting the final extract (Zucareli et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the allelochemicals present in sorghum tissues may vary in different parts of the plant. The allelopathic potential of S. bicolor can be used to control weeds by means of the application of sorghum residues as mulch or including sorghum cultivars in a crop rotation [32] According to Narwal et al [33], the infestation of monocotyledon weeds was reduced between 79 and 91%, and dicotyledon infestation was reduced between 84 to 100% when pearl millet was grown as a forage species. Competition and allelopathic effects performed, during the coexistence of the cover crop with the weeds can be responsible for the suppressive effect.…”
Section: Resultsmentioning
confidence: 99%
“…Zucareli et al [31], found that S. bicolor aqueous extract exerted a dose-dependent inhibitory effect on cabbage germination and initial growth. Extracts were obtained from pre-flowering plants (60 days after emergence), as also performed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Although U. ruziziensis and Sorghum bicolor L. Moench have been shown to exert inhibitory effects on the germination and growth of various weeds, including E. heterophylla [6,30,31], little is known about the biochemical effects of their allelochemicals on target weeds, particularly on mitochondrial metabolism. Given the herbicidal and growth regulatory effects of allelochemicals, added to the competition generated by allelopathic plants against weeds, it is crucial to identify which molecules act as allelochemicals and understand their action on plant cells.…”
Section: Introductionmentioning
confidence: 99%